Central pontine myelinolysis following pediatric living donor liver transplantation: A case report and review of literature. (12th April 2014) - Uchida, Hajime; Sakamoto, Seisuke; Sasaki, Kengo; Hamano, Ikumi; Shigeta, Takanobu; Kanazawa, Hiroyuki; Fukuda, Akinari; Nosaka, Shunsuke; Kubota, Masaya; Kasahara, Mureo
Abstract CPM is one of the most serious neurological complications that can occur after OLT and is characterized by symmetrical demyelinization in the basis pontis. The etiology of CPM remains unclear, although the rapid correction of the serum sodium and CNI concentrations may be associated with the development of CPM. With recent advances in MRI technology, early diagnosis of CPM has become possible. Here, we present the case of a five‐yr‐old female who developed CNI‐associated CPM after undergoing LDLT. A decreased level of consciousness and dysphasia was noted one wk after LDLT, and MRI revealed findings compatible with a diagnosis of CPM. The patient fully recovered from the neurological deficits related to CPM following the switch from the CNI to sirolimus. We propose MRI to be promptly considered for patients with abnormal neurological findings, together with the substitution of CNI with an mTOR inhibitor as a management regimen for CNI‐related CPM.